A Monte Carlo study of the Falicov-Kimball model in the perturbative regime - face=`Arial`>ł, Grzegorz Musia<font; face=`Arial`>ębski, Lech D<font; Wojtkiewicz, Jacek (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Finite-temperature properties of the Falicov–Kimball model on the square lattice have been studied in the perturbative regime, i.e. for t/U << 1, where t is the hopping constant and U denotes the Coulomb interaction strength. In our study, we have determined the phase diagram of the model in the second-order of the perturbation theory, where the antiferromagnetic Ising model in the magnetic field emerges. In the fourth-order,where our model constitutes the Ising model with more complicated frustrated antiferromagnetic interactions, the sketch of the phase diagram was established. The Monte Carlo method was employed and the behavior of Binder cumulants based on the order parameters was analyzed to determine the type of ordering and phase boundaries in the diagram.